2012
DOI: 10.1159/000337299
|View full text |Cite
|
Sign up to set email alerts
|

Human Tuberculous Meningitis Caused by <i>Mycobacterium caprae</i>

Abstract: Introduction: Tuberculous meningitis (TM) causes substantial morbidity and mortality in humans. Human TM has been known to be induced by bacteria from the Mycobacterium tuberculosis complex(MTBC), such as M. tuberculosis and M. bovis. Case Presentation: We describe a case of meningitis treated with fosfomycin, which showed partial effectiveness in an 80-year-old patient. After a lethal myocardial infarction, M. caprae (MC) was identified in cerebrospinal fluid culture. This isolated acid-fast organism was firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In European countries, patients with zoonotic tuberculosis suffered more from reactivation of old infections, which mainly leads to pulmonary tuberculosis. This could explain that only few cases due to M. caprae have been reported in detail in case reports: 2 cases of cuateous tuberculosis [10] , [11] and 1 each of pericarditis case [12] , urinary tract involvement [13] and meningitis [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In European countries, patients with zoonotic tuberculosis suffered more from reactivation of old infections, which mainly leads to pulmonary tuberculosis. This could explain that only few cases due to M. caprae have been reported in detail in case reports: 2 cases of cuateous tuberculosis [10] , [11] and 1 each of pericarditis case [12] , urinary tract involvement [13] and meningitis [14] .…”
Section: Discussionmentioning
confidence: 99%
“…El análisis del patrón de restricción obtenido sobre el producto de la amplificación del fragmento de 1020 pb de gyrB, previamente usado por Niemann, Kasai y Chimara, permitió, en primer lugar, descartar la presencia de un miembro del CMTB y, posteriormente, ubicar a la especie responsable del caso (Hansena, Seilera, Rumpfa, Krafta, Dlaskea, Abele-Hornb y Muellges, 2012).…”
Section: Gen Rpobunclassified
“…caprae has been reported as a cause of tuberculosis in humans in several countries (Hansen et al 2012;Goh et al 2006;Mostowy et al 2004;Muller et al 2013;Bayraktar et al 2011a;Bayraktar et al 2011b). Other animal adapted MTBC members are less frequently involved in the development of zoonotic tuberculosis.…”
Section: Epidemiology Of Other Members Of the Mycobacterium Tuberculomentioning
confidence: 99%
“…M. microti and M. cannettii have been described much earlier, but were for a long time believed to be pathogenic in murines and humans, respectively. Recent reports have shown that some of these organisms can infect and cause disease in other species as well and the full host range still needs to be defined (Aranaz et al 2003;van Ingen et al 2012;Alexander et al 2010;Dawson et al 2012;Hansen et al 2012;Pate et al 2006;Kiers et al 2008;Goh et al 2006;Mostowy et al 2004). …”
Section: Causative Agents Of Tuberculosis In Human and Animal Hostsmentioning
confidence: 99%